Influence of Chemical Reaction on Marangoni Convective Flow of Nanoliquid in the Presence of Lorentz Forces and Thermal Radiation: A Numerical Investigation - Ghulam, Rasool; Ting, Zhang; Anum, Shafiq; Hulya, Durur (Journal of Advances in Nanotechnology, 2019)
This study aims to numerically investigate the Marangoni convective flow of nanoliquid initiated by surface tension and heading towards a radiative Riga surface. The surface tension appears in the problem due to the gradients of temperature and concentration at the interface. The influence of first order chemical reaction is involved in the system with sufficient boundary conditions. Set of governing nonlinear PDEs is transformed into highly nonlinear ODEs using suitable transformations. HAM is applied for convergent series solutions. Impact of various pertinent fluid parameters on momentum, thermal and solutal boundary layers is analyzed graphically. The chemical reaction plays vital role in saturation of nanoparticles in the base fluid near the surface as well as away from it. The Lorentz forces originated by the Riga surface become powerful when the radiation parameter comes into effect. The significance of Riga plate is thus more prominent through thermal radiation. However, the magnetic effect dampens down for higher radiation parameter. Fluid parameters, Nusslt and Sherwood numbers are analyzed with detailed discussion and concluding remarks.
Keywords: Nanoparticles; Nanoliquid; Riga surface; Thermal radiation; Chemical reaction.